"The porphyrias in South Africa" A study of the excreted porphyrins - Sweeney, George Douglas (Division of Urology, 2020)
Study of the diseases of porphyrin metabolism has formed a major part of the work of the C.S.I.R.- U.C.T. Renal metabolic Research Group since 1959. The scope of the activities of this Group has been wide; this thesis concerns but one aspect, the excreted porphyrins. This is essentially a laboratory study but it is a study that would have lost much of its significance had it not been closely linked to the clinical studies of other members of the group, in particular Prof. L. Eales. The unit has formed a stimulating environment in which to pursue these investigations and it is a. pleasure to acknowledge the contributions to this thesis of all members of the group.